'What about me?' Stories of the educational experiences of care-experienced children and young people in a Scottish local authority. (July 2021) - Mercieca, Daniela; Mercieca, Duncan P; Randall, Leisa
This qualitative study explores the educational experiences of looked after children and young people in one Scottish local authority. The preoccupations of government are academic achievement and school attendance, but these are not the prime concerns of the children, carers and professionals involved. Moreover, they can be both enhanced and restricted by the background characteristics and care situations of the young people and the responses of schools to their needs and behaviour. Five influential factors emerged from interviews and focus groups with professionals, carers and young people: behaviour; school attendance; carers as educators; friendships; and communication between home and school. Each of them is discussed with extended quotations that convey the voices of participants.